A VIDEOSPECTRAL SYSTEM FOR EARTH'S REMOTE SENSING ON BOARD OF THE INTERNATIONAL SPACE STATION - Yu. A. Krot; A. V. Chumakov; V. F. Gusev (Приборы и методы измерений, 2015)
A videospectral system for Earth's remote sensing from space has been developed. The operating principle, optical scheme, basic and assist modules of the system are described. The specific requirements to device for ecological monitoring tasks at space experiments are presented. The main optical parameters of the experimental prototype have been analyzed. The method of gratings astigmatism correction has been developed. Optical parameters of the system have been improved.